A clinicopathological study and evaluation of significance of argyrophilic staining of nucleolar organizer regions in kidney tumours - Elavarasan, T.; Shruthi, M.S.; Sangeetha, N. (Tropical Journal of Pathology and Microbiology, 2019)
A variety of benign and malignant neoplasms arise in the kidneys of adults and children. With the advancement in the recognition of newer variants and wide spectrum of appearances of these tumours especially of nephroblastoma and renal cell carcinoma, the diagnostic accuracy and assessment of critical prognostic indicators for these tumours pose challenges to the surgical pathologists. The present spurt of interest in grading the tumours on morphological and histological criteria and correlating them with AGNOR counts and to the clinical outcome in terms of survival rates is mainly attributable to the recent innovations in surgical and medical oncology. In the present study each of the renal tumour samples were subjected to an argyrophilic staining for the nucleolar organizer region according to the modified colloidal silver technique. In Grade I, II & III renal carcinoma cases the AgNOR index was 0.875, 1.301, and 1.710 respectively. It has been observed that mean AgNOR indices are directly proportional to grading. i.e., with increased grades the mean AgNOR count also increased and can be used for assessing the clinical outcome and prognosis of the cases. The mean AgNOR scores in epithelial, mesenchymal, blastemal areas for all cases of Wilms’ tumour were 4.46, 4.82, and 5.76 respectively. Based on the mean AgNOR score it has been found that blastemal areas have higher score than mesenchymal and epithelial areas. The increased score in blastemal areas can be attributed to increased proliferative activity of the tumour. Prognostication is the most important contribution of the medical scientist to the suffering patient. The AgNOR scoring as a prognostic index helps the clinician in this.